A Field on the Move: Notes on the Recent Historiography of Late Ottoman Migrations in Turkish - Kerem Tınaz; Akın Sefer (Diasporas: Circulations, Migrations, Histoire)
This article gives an overview of the recent developments in the Turkish language literature on late Ottoman migration history throughout the last two decades. Highlighting a revival of academic interest on migration and mobility in Turkey, it focuses on the resurgence of scholarly studies on late Ottoman migration history. It underlines the significance of academic and institutional developments, as well as the sociopolitical context, in explaining the new dynamism in historical research on Ottoman migrations. It then makes a brief assessment of the limits and challenges of these studies as well as possible avenues for further research in Ottoman migration historiography.